An investigation into the potential of Singapore clays for use in studio ceramics - Kemp, Brian Francis. (2009)
In this investigative study, eighty previously untested Singapore clays were collected from various locations and subjected to a wide range of tests to determine their suitability for further development as studio bodies. Those that offered the most potential were further tested, blended and developed to create a range of bodies to allow potters to have as wide a choice as possible. These included a range of earthenware, and stoneware bodies, plus a basalt body.